Pain score comparison in patients receiving lignocaine gel 2% versus plain lubricating gel during flexible cystoscopy,a prospective randomized controlled trial,a crossover study. - Gawi, Syed Mohd Adli Syed Mohd Gawi (2017)
There is no clear evidence that intraurethral 2% lignocaine gel is superior to plain lubricating gel in reducing pain during flexible cystoscopy (Flex CE).Since 2% lignocaine gel is far more expensive than plain lubricating gel, our study aimed to compare pain score in patients receiving 2% lignocaine gel and plain lubricating gel during flexible cystoscopy (Flex CE).At the same time, the cost difference was also compared in order to asses the benefit of both groups. This is a randomize , prospective, single blind, cross over study. A total of 90 patients were involved in this study. The patients were then randomized by our computer generated randomization sequence to receive either 2% lignocaine gel (Group A) or plain lubricating gel (Group B). Initial 10ml of either 2% lignocaine gel or plain lubricating gel was instilled depending on the group assigned. Flexible cystoscopy was then inserted until the bladder mucosa is seen. Pain score was then recorded by Visual Analogue Score (VAS) with zero, 0 being no pain until 10 which is maximum pain. Additional 2% lignocaine gel was given to patients who requested to have additional gel if the pain was intolerable, regardless of the group assigned (cross-over study).The additional amount of 2% lignocaine gel and the subsequent final VAS score was also recorded. Besides, the cost difference between the two groups was also analyzed. Mean pain score for group A (2% lignocaine gel) was 4.53, while mean pain score for group B (plain lubricating gel) was 4.33.With a p value of 0.388,there was no statistically significant difference in pain score between the two groups. Patients’ characteristics in the two groups were homogenous. Twenty one patients from 2% lignocaine gel group required additional 2% lignocaine gel while 26 patients from plain lubricating gel group required additional 2% lignocaine gel. The mean cost for 2% lignocaine gel was RM12.30 compared with the mean cost for plain lubricating gel RM 9.44.Despite taking together the cost of additional lignocaine gel in plain lubricating gel group, there were still statistically significant cost difference with a p value of 0.008. The efficacy of 2% lignocaine gel is not superior compared to plain lubricating gel in reducing pain during flexible cystoscopy. The cost of 2% lignocaine gel was proven to be higher than the cost of plain lubricating gel with little difference in mean pain score.